THE RELATIONSHIP OF ENGLISH LEARNING IN PRIMARY SCHOOL - Amanov, Alisher (Журнал иностранных языков и лингвистики, 2023)
In our article, we will talk about classroom interaction, its importance, and its role in primary education. Next, we will talk about listening, speaking, reading, and writing skills, as well as development opportunities and the role of a communicative approach in teaching English to young people.